Impersonal and functionally impersonal verbs with the meaning of atmosphere-meteorological events in Lithuanian, Slovenian and Russian languages - Михайловна Коницкая, Елена (Slavistica Vilnensis, 2004)
The paper analyzes the lexical-semantic group of verbs that form impersonal sentences expressing environmental condition, by comparing Lithuanian, Slovenian, and Russian. The author points out similarities and distinctions in the three languages with respect to the structure of the verb groups, their internal composition, the features of the semantic structures formed by such verbs, and the morphological features of the verbs. In a number of cases Lithuanian and Slovenian address these issues similarly while in others, Lithuanian is closer to Russian.